Accuracy and Precision of a Point-of-Care HbA1c Test. (September 2020) - Arnold, William D.; Kupfer, Kenneth; Little, Randie R.; Amar, Meera; Horowitz, Barry; Godbole, Narendra; Hvidsten Swensen, Monica; Li, Yin; San George, Richard C.
Background: Point-of-care (POC) hemoglobin A1c (HbA1c) testing has advantages over laboratory testing, but some questions have remained regarding the accuracy and precision of these methods. The accuracy and the precision of the POC Afinion™ HbA1c Dx test were investigated. Methods: Samples spanning the assay range were collected from prospectively enrolled subjects at three clinical sites. The accuracy of the POC test using fingerstick and venous whole blood samples was estimated via correlation and bias with respect to values obtained by an NGSP secondary reference laboratory (SRL). The precision of the POC test using fingerstick samples was estimated from duplicate results by calculating the coefficient of variation (CV) and standard deviation (SD), and separated into its components using analysis of variance (ANOVA). The precision of the POC test using venous blood was evaluated from samples run in four replicates on each of three test cartridge lots, twice per day for 10 consecutive days. The SD and CV by study site and overall were calculated. Results: Across the assay range, POC test results from fingerstick and venous whole blood samples were highly correlated with results from the NGSP SRL ( r = .99). The mean bias was −0.021% HbA1c (−0.346% relative) using fingerstick samples and −0.005% HbA1c (−0.093% relative) using venous samples. Imprecision ranged from 0.62% to 1.93% CV for fingerstick samples and 1.11% to 1.69% CV for venous samples. Conclusions: The results indicate that the POC test evaluated here is accurate and precise using both fingerstick and venous whole blood.